FUNCTIONAL HYPOTHALAMIC AMENORRHOEA IN FEMALE ATHLETES - PATHOPHYSIOLOGY, RISK FACTORS, CONSEQUENCES AND POSSIBLE TREATMENTS - Julia Kulczycka,; Karolina Smolińska,; Zuzanna Perlicka,; Monika Dąbek,; Monika Gajda-Bathelt,; Katarzyna Jania,; Tomasz Antczak,; Paulina Sadkowska,; Weronika Popow,; Michał Ciołkosz, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Functional hypothalamic amenorrhoea is a prevalent endocrine disorder among female athletes, primarily caused by low energy availability (LEA). LEA induces a cascade of endocrine and neurohormonal changes, leading to disrupted GnRH pulsatility, anovulation, and hypoestrogenism. The health consequences of FHA are extensive, affecting bone density, cardiovascular function, fertility, and neuropsychiatric health.Purpose: The aim of this paper was to review FHA in female athletes, focusing on its pathophysiology, clinical consequences, diagnosis, and treatment, while emphasising the need for early detection and multidisciplinary care.Methodology: A narrative literature review was conducted using Google Scholar and PubMed. Relevant original research articles, systematic reviews, clinical guidelines, and authoritative textbooks were included to ensure comprehensive coverage of the topic.Conclusions: Untreated FHA leads to serious health consequences. Early diagnosis and timely intervention are critical. Multidisciplinary approach should be implemented. Further studies are needed particularly in the areas of early identification, pathophysiological mechanisms, and effective, evidence-based treatment strategies.